The disaster tourist : a novel - Eun, Yun Ko- 1980-; Buehler, Lizzie (Berkeley, California : Counterpoint, 2020)
For ten years, Yona has been stuck behind a desk as a coordinator for Jungle, a travel company specializing in vacation packages to destinations devastated by disaster and climate change. Her work life is uneventful until trouble arises in the form of a predatory colleague. To forestall any disruption of business-as-usual, Jungle makes Yona a proposition: a paid "vacation" to the desert island of Mui. But Yona must pose as a tourist and assess whether Jungle should continue their partnership with the unprofitable destination. Yona travels to the remote island, whose major attraction is an underwhelming sinkhole, a huge disappointment to the customers who've paid a premium. Soon Yona discovers the resort's plan to fabricate a catastrophe in the interest of regaining their good standing with Jungle--and the manager enlists Yona's help. Yona must choose between the callous company to whom she's dedicated her life, or the possibility of a fresh start in a powerful new position. As she begins to understand the cost of the manufactured disaster, Yona realizes that the lives of Mui's citizens are in danger--and so is she.
"First published in Great Britain in 2020 by Serpent's Tail, an imprint of Profile Books Ltd."--Title page verso.
Keywords: Dark tourism -- Fiction; Climatic changes -- Fiction; Travel agents -- Fiction; Tourism -- Employees -- Fiction; Tourism -- Korea (South) -- Fiction; Islands -- Vietnam -- Fiction; Vietnam -- Description and travel -- Fiction